Lightweight Adherence Prediction and Justification for Government Strategic Priorities - Utino, Matheus; Gôlo, Marcos; Turine, Marcelo; Marcacini, Ricardo (Anais do Latin American Symposium on Digital Government (LASDiGov); 2026: Anais do XIV Latin American Symposium on Digital Government, 2026)
The Brazilian National Postgraduate System plays a strategic role in scientific development and policymaking. The CAPES National Agenda organizes 470 strategic themes into 20 macro-themes, reflecting priorities from Brazil’s 27 Federative Units. Given the large annual volume of academic outputs, identifying their alignment with these priorities is essential. This study evaluates lightweight machine learning models as scalable alternatives to LLMs for adherence prediction and justification. Using 42,026 academic outputs and nine classifiers, Bag-of-Words with Random Forest achieved competitive performance (F1 of 0.755), outperforming semantic embeddings. A fine-tuned PTT5-base produced explanations highly similar to human references.